Manajemen Isu Komunisme dalam Bingkai Nasakom di Era Soekarno (1959-1966) - Sjuchro, Dian Wardiana; Besman, Abie (Universitas 17 Agustus 1945 Surabaya, 2020)
AbstractThis research focuses on the management issue of communism in the Nasakom framework through the policies and patterns of political communication of President Soekarno's government. This issue was used by Soekarno since the 1959 Presidential Decree. The solution implemented by Soekarno unwittingly opened a space for political communication in the middle way. Compromise management style is used to suppress conflicts that occur between interests. The method used in this study is the historical method. The results showed that the approach adopted by President Soekarno could not be separated from Communism. Even though it seemed to unite all the ideologies that were developing at that time, in fact there was a very sharp political competition between factions. This then led to the events of 30 September and the emergence of a new order. This research is part of a broader study to examine the management of communism issues in every political regime in Indonesia. Keywords: Nasakom, Issue Management, Communism, Literature Study